User Participation and Insight among Mentally Ill Individuals: Stories from District Psychiatry Centres in Northern Norway - Klausen, Rita Kristin (Sage, 2014)
Source: doi:10.4135/978144627305013509045 The purpose of this text is to describe the beginning of a qualitative study related to user participation and insight among mentally ill individuals. The term ‘user’ describes a patient who is not a passive recipient, but an active user of services. The study uses a narrative methodology and includes 30 in-depth interviews with consenting participants who have experienced serious changes in their lives because of their disease and who have experienced one (or more) hospitalization because of their disorder. Through a pilot interview with a user patient, who became a co-researcher and consultant for a very short period of time, the interview guide changed. During the interviews, I realized that the results would be different than first expected. Unexpected challenges arose in relation to the interviews as three of the participants were refugees who had been denied their applications for asylum. I had prepared myself for interviews with patients who were well acquainted with the Norwegian treatment culture. Telephone interpreters were needed, and the interview situation changed. Dilemmas related to the role of the researcher emerged. It was difficult to be a researcher, and exclude the therapist role. Reflexivity proved necessary throughout the research process; by exploring what happened during each interview, I came closer to see what shaped my research results. A reflexive approach proved to be fruitful in the process of constructing of knowledge.